Guillain-Barre Syndrome: A Case Report - Nikunja Basini Pati; Ruksana Begum; Salome Satya Vani. P; Soujanya R (Journal of Tropical Pharmacy and Chemistry, 2019)
Guillain-Barre syndrome (GBS) is a complicated degenerative neurological disorder which can be acute or chronic in nature. It is an acquired condition which is characterized by progressive, symmetrical, proximal and distal tingling and weakness. Muscle stretch reflexes are decreased to absent and loss of sensation is common. Etiology remains unclear but pathophysiology includes demyelination of spinal nerve roots. Death is rare. Early diagnosis and prompt referral should occur in severe cases due to the incidence of potential ventilation failure and cardiovascular instability in some patients. The case of a 26-year-old male presenting to a physician is described. The importance of a correct diagnosis by the physician and the subsequent management is reviewed. Key words: Guillain-Barre syndrome, extremity weakness, peripheral nerves, trauma